Dependence of Structural and Optical Properties of ZnO Thin Films Grown by Sol-Gel Spin-Coating Technique on Solution Molarity - Chala, Slimane; Bdirina, Madani; Elbar, Mourad; Naoui, Yassine; Benbouzid, Yazid; Taouririt, Taki Eddine; Rahmane, Saad (Springer, 2022)
Zinc oxide (ZnO) thin films were deposited on glass substrates by using sol-gel spin coating technique. Zinc acetate dihydrate and 2-methoxyethanol were used as precursor with different molar concentrations, 0.2 M, 0.3 M and 0.6 M. The effect of precursor concentration on the structural and optical properties, transmission (T), reflection (R), optical bandgap (Eg), Urbach energy (E-U), refractive index (n), extinction coefficient (k), single-oscillator energy (E-0), dispersion energy (E-d), moments M-1 and M-3, dielectric constant (epsilon) and optical conductivity (sigma), of the ZnO thin films was studied and investigated. Although, the transmittance, slightly, decreased and the reflectance increased, as the molar concentration increased, the measurements showed that all samples have high transparency and low reflectivity in the visible range which make them suitable for solar cells applications. It is also found that, as the molarity increased, the ZnO thin films exhibited lower Eg and E-U and higher Ed, M-1 and M-3.
Keywords: Sol-gel; ZnO; Molarity; Thin film; Optical properties